Soil moisture uncertainty in models - Brown, M; Quaife, T; Black, E (Joint UK Land Environment Simulator (JULES), 2015)
This project aimed to understand uncertainty in land surface model (LSM) predictions of soil moisture (SM) over Africa, which is a result of uncertainty in the prescribed rainfall and soil parameters. To investigate the rainfall uncertainty a realistic range of rainfall scenarios for 2008 were run through an LSM. The daily rainfall timing and intensity was varied to see if this impacted the uncertainty. The highest uncertainty occurred when the daily rainfall was split over 3 hours instead of 1. The soil parameter uncertainty was investigated by varying model soil parameters within observed limits. This was by far the largest source of uncertainty.